Implementation of think pair square type cooperative learning to improve collaboration skills in high schools - Nurkanti, Mia; Kulsum, Umi; Halimah, Dewi (Universitas Wiralodra, 2024)
Think Pair Square Style Cooperative Education encourages each student to become a proficient and independent learner. Given that this learning emphasizes 21st-century skills such as critical thinking, creativity, and teamwork. It was such as necessary to assess how effectively the application of this method enhances students' critical thinking abilities in the real world. The objective of this project is to improve student cooperation in cell biology classes by implementing a cooperative learning model similar to the Think Pair Square. The Classroom action research model was developed by Kemmis and McTaggar, which served as the framework for the procedure employed in this study. The outlines of the four stages of classroom action research are technique—planning, implementation, observation, and reflection. This instructional approach is seen to be beneficial as it enables students to share their thoughts and helps them see alternative problem-solving approaches. Students can seek explanations from other students to explain how to solve the problem if they are struggling with that. From the Data results, there were rising scores in the form of scoring that serve as evidence for this. Students' collaboration skills scored an average of 1.6 (level 1, or basic level) in the pre-cycle, 2 (level 2, or medium level), and 3.56 (level 3, or trained level) in cycle 2. Think Pair Square's implementation at SMA in Bandung could improve collaboration both within and outside of the classroom, foster more active dialogue and idea exchange, and promote student contact.